Biodiversity monitoring and conservation: bridging the gap between global commitment and local action.(Book review) - Huettmann, F (Choice (Middletown), 2014)
This thorough book, based on a symposium held at the Zoological Society of London, is impressive in terms of the range of topics covered. The book's 18 chapters address subjects such as species changes, various impacts on biodiversity, and new methods for monitoring biodiversity. The 63 international contributors present a classic approach to monitoring biodiversity components as applied to modern challenges and policies.